Analysis of confidentiality of information transfer in DSSS systems in conditions of limited systems of used signal constructions - Голубничий, Олексій Георгійович (Ukrainian Information Security Research Journal, 2019)
Information security in telecommunications can be provided at the physical level of telecommunication systems by means of energy and structural secrecy of information transfer. Spread-spectrum telecommunications, in particular the DSSS (Direct Sequence Spread Spectrum) technique, are the most suitable for the implementation of such approach to information security. Ensuring the necessary level of structural secrecy of information transfer using DSSS technique is that this technique uses systems of signal constructions with a sufficiently large number of signals in the system. There are requirements to correlation properties of each such signal construction, because in accordance with the Wiener-Khinchin theorem they determine the spectral characteristics of signals in a telecommunication system and, as a result, the structural spectral and energy secrecy of information transfer. The problem boils down to the fact that the systematic deterministic methods for synthesizing systems of signal constructions with a low peak sidelobe level of the autocorrelation function for the case of an arbitrary length of signal constructions and the number of ones in the system of signals are unknown, and the complexity of this problem is associated with an algorithmic undecidability of arbitrary algebraic Diophantine equations. The confidentiality of information transfer at the physical level of DSSS telecommunication systems while using some known systems of signal constructions with a low peak sidelobe level of the autocorrelation function and in the case of attacks, which are performed by an unauthorized user by means of optimal signal processing methods (optimal detection of biorthogonal signals), is analyzed in the article.